Enhanced Cryogenic Magnetocaloric Performance in Te Doped Dy2O3. (1st August 2022) - Abhinav E, Meher; Jaison, D.; Baskaran, P; Pavan Kumar, N.; Rao, Subha Krishna; Shanker, J.; Saravanan, L.; Gopalakrishnan, C.
Abstract : The work aims to investigate the magnetocaloric effect (an eco-friendly and energy-efficient cooling technique) of Te doped nanosized dysprosia, which could be used as the best alternative for conventional chlorofluorocarbons based refrigeration systems. In this present work, Te doped nano-sized dysprosia (TNSD) is synthesized using the sol-gel technique. The particle characteristics and magnetocaloric properties of TNSD were investigated. The change in lattice parameters of NSD concerning doping of TNSD is analyzed by using Rietveld refinement. The synthesized nanoparticles were observed to be spherical and monophasic with a Ia-3 structure. At low temperature, the sample exhibited a non-saturated magnetic behavior due to the co-existence of ferromagnetic and antiferromagnetic phases, while at high temperature it exhibited a paramagnetic nature. The maximum entropy change of TNSD at a magnetic field of 50 kOe was found to be 30.6 JKg −1 K −1 . The significant magnetic transitions at low temperature and large magnetic entropy change make TNSD suitable material as a refrigerant for cryo-cooling systems.